2015
DOI: 10.1080/00015458.2015.11681129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraperitoneal Thymoquinone on Postoperative Peritoneal Adhesions

Abstract: Based on the results of this study in a rat peritoneal adhesion model, intraperitoneal administered thymoquinone has a strong anti-adhesive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The grade of inflammation, hydroxyproline content were also significantly lower in the TQ administered group. These findings were correlated with the total antioxidant capacity of the samples which were significantly higher in the TQ administered group showing that the antioxidant effect of TQ is also responsible for the reduction in peritoneal adhesion scores in the TQ group [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The grade of inflammation, hydroxyproline content were also significantly lower in the TQ administered group. These findings were correlated with the total antioxidant capacity of the samples which were significantly higher in the TQ administered group showing that the antioxidant effect of TQ is also responsible for the reduction in peritoneal adhesion scores in the TQ group [28]. …”
Section: Discussionmentioning
confidence: 99%
“…As our study demonstrated, it can be assumed that the anti-inflammatory and immunomodulator effect of TQ can be a result of its action on the anastomotic healing. In a study by Bozdag et al, intraperitoneally applied TQ was shown to decrease the hydroxyproline level and intraabdominal adhesions (Bozdag et al 2015 ). In the present study, orally administered TQ was demonstrated to increase the hydroxyproline levels on the anastomotic line.…”
Section: Discussionmentioning
confidence: 99%
“…Through the inhibition of prostaglandin and thromboxane, NSAIDs decrease vascular permeability, inhibitors of plasmin, platelet aggregation, coagulation and increase macrophage activity. NSAIDs modulate different aspects of inflammation and reduce the formation of adhesions in most animal models [ 39 ]…”
Section: Management and Preventive Strategies For Adhesionsmentioning
confidence: 99%